Evaluation of functional activity of patients with chronic venous insufficiency and leg ulcer - Szewczyk, Maria T.; Jawień, Arkadiusz; Cierzniakowska, Katarzyna; Cwajda, Justyna; Kędziora-Kornatowska, Kornelia; Mościcka, Paulina; Grzeszak, Ilona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
The aim of the study was to evaluate an activity of elderly patients in aspect of everyday functionning. The influence of chronic venous insufficiency and its complications on the degree of independence of patients treated due to leg ulcer was assesed Material and methods: Study was conducted in 2004 and 2005 among 76 patients treated in Venous Leg Ulcer Outpatient Clinic of Chair and Clinic of Surgery and patients hospitalized in Chair and Clinic of Geriatry – Medical University in Bydgoszcz. Mean age of patients was 73,9 years (±8,51). Patients were divided into two groups – with and without ulcers. Activity of patients in aspect of basic everyday functions was assesed. Measurement tool was ADL scale (Activity of Daily Living), third part of EASY-Care (Elderly Assessment System) questionnaire. Results: Mean scores and medians of both groups confirmed the existence of significant differences – mean score of patients with ulcer was 19 points higher (p<0.05) than patients without ulcers. Conclusion: Chronic venous insufficiency and its terminal state – venous ulcer significantly worsen activity of patients in aspect of everyday living.